ANALISA BIAYA DAN WAKTU DENGAN MENGGUNAKAN METODE TIME COST TRADE OFF PADA PROYEK PEMBANGUNAN HOTEL ASTON PARAMOUNT MALANG - Iktiva Sani; Zamzami Septiropa (Media Teknik Sipil, 2014)
ANALISA BIAYA DAN WAKTU DENGAN MENGGUNAKANMETODE TIME COST TRADE OFF PADA PROYEKPEMBANGUNAN HOTEL ASTON PARAMOUNT MALANGIktiva Sani1, Zamzami Septiropa21,2Jurusan Teknik Sipil Fakultas Teknik – Universitas Muhammadiyah MalangAlamat korespondensi : Jalan Raya Tlogomas 246 Malang 65144ABSTRACTImplementation of Development Projects Aston Paramount delayed completion time causedby the discharge of water continuously from the underground, thus flooding the area GWT (GroundWater Tank), STP (Sewage Treatment Plan) and the destruction of Tower Crane. It can be based ontime schedulle project in November 2012 or at the time the project reaches 17 weeks, the progressof the plan should reach 28.648%, but the reality on the ground has reached 24.194%, so it can beknown deviation -4.454%.The method applied in this thesis Time Cost Trade Off (TCTO) to speed up implementation ofthe project in order to achieve the optimum time in the rest of the work project. TCTO a time andBiya exchanges with a view to speeding up the duration.Acceleration time is done by holding the shift work. Of the project schedule has been delayed,the rest of the project is completed within 180 days for a total cost of Rp. 32,679,810,571.24.However if the project accelerated by using TCTO to return to the original plan schedule is 162days obtained a fee of Rp. 33,462,446,260, the difference between the cost of Rp. 782,635,689.88.Keywords: Time and Cost